Systematic literature review: pengembangan kemampuan berpikir kritis siswa melalui pembelajaran discovery learning - Nuridayah, Fadilla; Sugandi, Asep Ikin; Kadarisma, Gida (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This study aims to determine whether it is able to improve students' critical thinking skills in learning mathematics by using the discovery learning model. This study uses the SLR model or Systematic Literature Review. The stages in this method are planning, review and documentation with data grouping, data analysis and data conclusion. This study obtained results showing that: One alternative teacher in learning mathematics in order to improve students' critical thinking skills is to use the Discovery Learning learning model.